RADIO BROADCASTING TRAINING SMANSAMAN AT SMA NEGERI 1 MANYARAN WONOGIRI - Betty Gama; Hariyanto -; Henny Sri Kusumawati (Universitas Muhammadiyah Semarang, 2017)
Smansaman Radio 106.1 FM is a learning radio of SMA Negeri 1 Manyaran Wonogiri, which is already established two years ago. Radio is intended for students, who take an extracurricular lesson of Radio Broadcasting. Problems faced are the limited guidance, mentoring and knowledge of teachers related to the issue of knowledge in the field of radio, causing the announcer to work according to their ability and experience of each student. Community service activity program held for two days and aims to provide training in radio broadcasting for students to know, understand and appreciate the techniques of radio broadcasts and managing radio broadcasts. Whereas specific target activity is increasing job skills and the development of character in creativity and innovative of the student to move in the field of radio broadcasting. Material presented on the radio broadcast technique, broadcast personality training and radio media management. Training provided using lectures method, discussions, voice testing, taste testing, imagination testing and practicing in the radio studio. The results of community service activity showed the average value of pre test 73.75, while the average value of post test of 89.58 or increased 21.46% of the total participant activity.Keywords: Training, broadcasting, radio, SMA.